(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
Today, the rapid development of industry and the uncontrolled use of chemical fertilizers in agriculture have led to the contamination of soil and water with heavy metals. Metals such as Pb, Cd and Hg do not decompose in the soil and have the property of bioaccumulation (accumulation). This not only endangers the plant world, but also human health through the food chain, which determines the relevance of the topic on a global scale.